Immunocytotoxicity, cytogenotoxicity and genotoxicity of cadmium-based quantum dots in the marine mussel Mytilus galloprovincialis - Lopes Rocha, Thiago (2020)
There is an increased use of Quantum Dot (QDs) in biological and biomedical applications, but little is known about their marine ecotoxicology. So, the aim of this study was to investigate the possible immunocytotoxic, cytogenotoxic and genotoxic effects of cadmium telluride QDs (CdTe QDs) on the marine mussel Mytilus galloprovincialis. Mussels were exposed to 10 μg L(-1) of CdTe QDs or to soluble Cd [Cd(NO3)2] for 14 days and Cd accumulation, immunocytotoxicity [hemocyte density, cell viability, lysosomal membrane stability (LMS), differential cell counts (DCC)], cytogenotoxicity (micronucleus test and nuclear abnormalities assay) and genotoxicity (comet assay) were analyzed. Results show that in vivo exposure to QDs, Cd is accumulated in mussel soft tissues and hemolymph and induce immunotoxic effects mediated by a decrease in LMS, changes in DCC, as well as genotoxicity (DNA damage). However, QDs do not induce significant changes in hemocytes density, cell viability and cytogenetic parameters in opposition to Cd(2+). Soluble Cd is the most cytotoxic and cytogenotoxic form on Mytilus hemocytes due to a higher accumulation of Cd in tissues. Results indicate that immunotoxicity and genotoxicity of CdTe QDs and Cd(2+) are mediated by different modes of action and show that Mytilus hemocytes are important targets for in vivo QDs toxicity.